PROJECT BASED LEARNING AS A MEDIA FOR ACCELERATING THE ACHIEVEMENT OF PROFIL PELAJAR PANCASILA IN THE PROGRAM SEKOLAH PENGGERAK - Wasimin Wasimin (Bajang Institute, 2022)
One of the characteristics of the Merdeka Curriculum implemented in the Program Sekolah Penggerak is the existence of project-based learning. The purpose of this study was to analyze the application of project-based learning as a medium for accelerating the achievement of the Profil Pelajar Pancasila in the Program Sekolah Penggerak. The research method used is descriptive analytical-qualitative. Several principals, teachers, and students in four schools in Klaten District were observed and interviewed for data collection. Document studies were conducted to strengthen the data. The validity of the data using triangulation and data analysis using the Colaizzi method. The results of the study indicate that project-based learning can be a medium to accelerate the achievement of the Profil Pelajar Pancasila, this is evidenced by the achievement of the Pancasila student dimension in each theme chosen by the school. Project-based learning can increase students' understanding of the material studied from various scientific perspectives and can develop students' skills and character.